PENGARUH MOTIVASI, PERSEPSI DAN SIKAP TERHADAP KEPUTUSAN MENGINAP DI HOTEL SYARIAH KOTA BANDUNG - Fitrianty, Rattikah; Danurdara, Ananta Budhi; Safari, Atang Sabur (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
This research is to find out the influence of motivation, perceptions and attitudes of consumers towards the decision to stay in a sharia hotel in Bandung. The sampling technique used accidental sampling of 100 respondents. The locus of this research is the Sharia hotel in Bandung. This research uses a quantitative approach with explanatory research design, this research is designed aimed at establishing the relationship of influence between the variables studied, therefore this research is referred to as correlational research, and using path analysis techniques. This research data collection method uses a survey method using a questionnaire. From the results of data processing carried out that the test results showed that partially Motivation factor (X1) to the decision of visiting customers (Y) was 0.25%, for the influence of Perception (X2) on the decision to stay overnight (Y) by 35.7%, and for the influence of attitude (X3) on the decision to stay by 10.3% and for the influence of Motivation (X1), Perception (X2) and attitude (X3) towards the decision to stay (Y) by 72.6%. Implications of sharia hotel research need to improve services and products related to consumer perception, which include performance, product and service features and quality of products and services, as well as the need for improvements in marketing, and renewal that adjusts both in terms of facilities and infrastructure in order to attract consumers and more.